Towards the Role of Test Design in Programming Assignments - Scatalon, Lilian Passos; Prates, Jorge Marques; De Souza, Draylson Micael; Barbosa, Ellen Francine; Garcia, Rogerio Eduardo [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2017)
Software testing can be very helpful to students if adopted in programming assignments throughout the Computer Science curriculum. Many testing practices involve students writing their own test cases. This approach implies that students are responsible for the test design task while performing the test activity. On the other hand, some testing practices follow the opposite approach of providing ready-made test cases, so students only need to execute and evaluate test results for their solution code. In this paper, we investigated the effect of test design in student programming performance. We conducted an experiment comparing two different testing approaches during programming assignments: student-written and instructor-provided test cases. We also assessed students' perceptions of this subject by means of a survey. Results suggest that when students are responsible for test design, i.e. when they write their own test cases, they perform better in programming assignments.
Keywords: Instructor-provided Tests; Programming Assignments; Software Testing; Student-written Tests; Test Design